Strategi komunikasi pemasaran PT. Duta Intidaya Watson Indonesia dalam memasarkan produk kesehatan - Asep Saifudin Asep Saifudin; Fadilah Fadilah; Henny Risnawati Henny Risnawati (LPPM Swadaya Institute of Business and Communication, 2023)
The success of a company in winning the competition does not only come from the right strategy but also comes from the efficiency of the company in formulating strategies. In this study, the author will conduct research on the Strategy and Communications used by PT. Watson's Intidaya Ambassador. Tbk. in marketing health products in Bekasi. As one of the multinational companies engaged in the FMCG industry. Watson Indonesia is a competitive company. Overall this thesis provides an overview of the strategy and communication of PT. Watson in marketing health products. In this campaign, Watsons wants to introduce to customers that Watsons also has a private-label product called the Watsons brand. In addition, Watsons also wants to show customers that the products offered by the Watsons brand are of good quality. It is tested to be made from natural, quality ingredients and has been dermatologically tested so it is safe to use. Marketing Public Relations analyzes both current and future problems. So one of the strategies used by the company's marketing is the Watson Try Me Love Me campaign. The marketing communication strategy carried out by the company certainly requires the media as a liaison between the company and its public. Therefore, in the Watsons Try Me Love Me campaign the media strategies used are offline media and online media. Watsons Indonesia tends to use social media so the most frequently used promotional media for this campaign is online media compared to offline media. Watsons Indonesia has its own social media, namely Facebook, Instagram, Twitter, Website, and Mobile apps.